Problems of Realization Women’s Right to Policy in the Republic of Kazakhstan - A. U. Tanalinova (Сибирское юридическое обозрение, 2012)
The article considers the problems of realization women’s right to policy in the Republic of Kazakhstan. The author reviews the different methods of political quota, which are used in some countries of the world. Besides that the author reveals the reasons of the women’s low political activity in Kazakhstan.